Three new species of Gliocephalotrichum causing fruit rot on different hosts from Brazil - Pereira de Almeida, Camila (2020)
The genus Gliocephalotrichum (Nectriaceae), originally described as a soil-borne fungus, has been associated with postharvest diseases, especially of tropical fruits. Taxonomic studies using both morphological and molecular phylogenetic analyses have contributed to recognition of novel species in several countries. However, in Brazil, only three isolates of Gliocephalotrichum have been collected from soil samples and roots since the late 1970s. Our study expands the sample range using many Gliocephalotrichum isolates obtained from rotting fruits of tropical plant species in different states of Brazil. Polyphasic taxonomy was assessed with phylogenetic analyses of DNA sequences from four nuclear loci, morphological comparisons, and pathogenicity tests. As a result, three known species (G. bulbilium, G. longibrachium, and G. simplex) were identified from new hosts and locations in Brazil. In addition, three new species are described—G. abrachium, G. brasiliense, and G. caryocaris. A key to all Gliocephalotrichum species worldwide is provided. Although species of Gliocephalotrichum have not been considered to be important plant pathogens, this study shows they may cause postharvest fruit rot in tropical fruits and therefore have an impact in communities that depend economically on the harvest and sale of these fruits.